2022
DOI: 10.1177/13506501221121930
|View full text |Cite
|
Sign up to set email alerts
|

Modeling harmonic drive with small deformation of flexspline and assessment of tooth wear by sliding coefficient

Abstract: Reducing the flexspline (FS) deformation is important for decreasing the alternating stress, flare angle in the axial direction, spatial deformation of teeth, and tube length. However, it may increase the probability of insufficient engagement depth and nonexistent conjugate tooth profiles. In this study, a mathematical model of the harmonic drive (HD) with a new tooth profile is proposed to reduce the FS deformation while satisfying the engagement depth and existence of a conjugated tooth profile. First, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…A boundary point on this circular arc, the end of the meshing tooth profile, can be calculated according to the principle that a point on the tooth profile of CS in which θ takes the maximum is meshed with this boundary point. 30 Let the transition tooth profile be devised as a straight line, the FS tooth profile is obtained by smooth connection between the straight line and the boundary point, as shown in Figure 4.…”
Section: Theoretical Modeling Of Hr With Small Transmission Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…A boundary point on this circular arc, the end of the meshing tooth profile, can be calculated according to the principle that a point on the tooth profile of CS in which θ takes the maximum is meshed with this boundary point. 30 Let the transition tooth profile be devised as a straight line, the FS tooth profile is obtained by smooth connection between the straight line and the boundary point, as shown in Figure 4.…”
Section: Theoretical Modeling Of Hr With Small Transmission Ratiomentioning
confidence: 99%
“…In summary, although reducing the radial deformation coefficient can improve the spatial deformations of teeth and shorten the axial length of device, it will reduce the load capacity and service life of the HR. 30 So how to increase the engagement depth and reduce the pressure angle is a challenge under the condition of reducing the radial deformation coefficient.…”
Section: Wg With New Profilementioning
confidence: 99%
See 1 more Smart Citation
“…(2015) found that the contact pair wear between wave generator (WG) and FS is adhesive wear, which is an alternating process of metal plastic flow, adhesion, slide and shear (Wen, 2018). Yu et al. (2023) designed a HD double-circular-arc tooth profile, and verified the advantage of this tooth profile by the tooth wear evaluation of FS/CS based on the sliding coefficient.…”
Section: Introductionmentioning
confidence: 95%
“…Li et al (2015) found that the contact pair wear between wave generator (WG) and FS is adhesive wear, which is an alternating process of metal plastic flow, adhesion, slide and shear (Wen, 2018). Yu et al (2023) designed a HD double-circular-arc tooth profile, and verified the advantage of this tooth profile by the tooth wear evaluation of FS/CS based on the sliding coefficient. However, the aforementioned literature did not consider the contact pairs wear of WG/FS and FS/CS comprehensively, nor did it involve research on the influence of wear on the meshing stiffness of HD.…”
mentioning
confidence: 95%